Hydrogen gas sensing using aluminum doped ZnO metasurfaces. Issue 8 (6th July 2020) - Chatterjee, Sharmistha; Shkondin, Evgeniy; Takayama, Osamu; Fisher, Adam; Fraiwan, Arwa; Gurkan, Umut A.; Lavrinenko, Andrei V.; Strangi, Giuseppe
Abstract : Hydrogen (H2 ) sensing is crucial in a wide variety of areas, such as industrial, environmental, energy and biomedical applications. In this work, aluminum-doped zinc oxide (AZO) nanotubes are reported for optical hydrogen sensing. Abstract : Hydrogen (H2 ) sensing is crucial in a wide variety of areas, such as industrial, environmental, energy and biomedical applications. However, engineering a practical, reliable, fast, sensitive and cost-effective hydrogen sensor is a persistent challenge. Here we demonstrate hydrogen sensing using aluminum-doped zinc oxide (AZO) metasurfaces based on optical read-out. The proposed sensing system consists of highly ordered AZO nanotubes (hollow pillars) standing on a SiO2 layer deposited on a Si wafer. Upon exposure to hydrogen gas, the AZO nanotube system shows a wavelength shift in the minimum reflectance by ∼13 nm within 10 minutes for a hydrogen concentration of 4%. These AZO nanotubes can also sense the presence of a low concentration (0.7%) of hydrogen gas within 10 minutes. Their rapid response time even for a low concentration, the possibility of large sensing area fabrication with good precision, and high sensitivity at room temperature make these highly ordered nanotube structures a promising miniaturized H2 gas sensor.